Optimization of Explosive Loads for Controlling Ground Vibrations in Blasting Activities at PT Riung Mitra Lestari, Jobsite Energi Batu Hitam, East Kalimantan - R Anggara; Xevarel Nevaldo Rayva Nugroho; Suparno; Fadilla Muhamad; Dhia Fahri (Jurnal Ilmu Multidisiplin, 2025)
This study aims to optimize the explosive charge to minimize ground vibration generated by blasting operations at PT Riung Mitra Lestari, Energi Batu Hitam Jobsite, East Kalimantan. According to the Indonesian National Standard (SNI 7571:2023), the permissible ground vibration limit is 5 mm/s. However, the company implements a more stringent internal limit of 4 mm/s for all types of structures as a preventive measure to mitigate potential damage and ensure safety and comfort for surrounding communities. Field measurements indicated that vibration levels exceeded the established limits, with values of 21.68 mm/s at the explosive magazine area (250 m from the blast site) and 7.168 mm/s at residential areas (326 m from the blast site). This evaluation employs a scaled distance approach and Peak Vector Sum (PVS) analysis based on the United States Bureau of Mines (USBM) empirical method. A regression model was developed to establish the relationship between scaled distance and PVS, which was subsequently used to predict Peak Particle Velocity (PPV) values derived from the obtained constant and exponent. The regression demonstrated a strong correlation, with a constant (k) of 9410.6, an exponent (e) of ?1.999, and a coefficient of determination (R²) of 0.8646. Based on these findings, the maximum recommended explosive charge to maintain PPV below 4 mm/s is 41.3 kg/hole for residential areas and 25.7 kg/hole for the explosive magazine area, adjusted according to the blasting geometry. The proposed design yields a Scaled Depth of Burial (SDOB) classified as “controlled energy,, which is in accordance with company standards. This study provides a safer and standardized blasting design alternative to minimize the risk caused by vibrations on the surrounding infrastructure.